The clinical correlation between Alzheimer's disease and epilepsy - Zhang, Dandan; Chen, Siyuan; Xu, Shoucheng; Wu, Jing; Zhuang, Yuansu; Cao, Wei; Chen, Xiaopeng; Li, Xuezhong (Frontiers in Neurology, 2022)
Previous study has suggested that epilepsy is a common complication of late dementia, and is a result of neurodegenerative diseases. Recent studies have found that seizures can occur in the early stages of Alzheimer's disease (AD). Furthermore, individuals with a history of epilepsy may have a higher risk of developing AD. Long-term repeated epilepsy, such as temporal lobe epilepsy, can cause cognitive impairment, which can lead to AD, and is often the cause of neurodegenerative lesions. Therefore, AD and epilepsy are inter-associated diseases, and they may have a common pathogenesis. Many studies have evaluated the shared pathogenesis and clinical relevance of AD and epilepsy. In this review, we discuss the clinical links between AD and epilepsy, including incidence, clinical features, and electroencephalogram (EEG) abnormalities. We summarized clinical studies between the two disorders in recent years. We also review new antiepileptic drugs as treatments for AD.